2017
DOI: 10.1007/s10803-017-3043-2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Utility of the ADI-R and DSM-5 in the Assessment of Latino Children and Adolescents

Abstract: Latino children in the US are systematically underdiagnosed with Autism Spectrum Disorder (ASD); therefore, it is important that recent changes to the diagnostic process do not exacerbate this pattern of under-identification. Previous research has found that the Autism Diagnostic Interview-Revised (ADI-R) algorithm, based on the Diagnostic and Statistical Manual of Mental Disorder, Fourth Edition, Text Revision (DSM-IV-TR), has limitations with Latino children of Spanish speaking parents. We evaluated whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…To illustrate, a study amongst a Somali population living in the UK (Fox, Aabe, Turner, Redwood, & Rai, 2016) reported findings that echo reports from populations resident in the horn or East of Africa (Gona et al, 2016;Tekola et al, 2016;Tilahun et al, 2016) regarding the perceptions of autism, experiences of stigma and unmet needs. Ethnic minority groups in high-income countries tend to be under-diagnosed for ASD and under-represented in autism research populations (Decoteau, 2017;Kawa et al, 2016;Sandy Magaña & Vanegas, 2017).…”
Section: <Table 1 Here>mentioning
confidence: 99%
“…To illustrate, a study amongst a Somali population living in the UK (Fox, Aabe, Turner, Redwood, & Rai, 2016) reported findings that echo reports from populations resident in the horn or East of Africa (Gona et al, 2016;Tekola et al, 2016;Tilahun et al, 2016) regarding the perceptions of autism, experiences of stigma and unmet needs. Ethnic minority groups in high-income countries tend to be under-diagnosed for ASD and under-represented in autism research populations (Decoteau, 2017;Kawa et al, 2016;Sandy Magaña & Vanegas, 2017).…”
Section: <Table 1 Here>mentioning
confidence: 99%
“…There are equivalence inconsistencies even with gold standard instruments such as ADI-R and ADOS-G. Specifically, Latino adolescents and adults with autism show lower levels of restrictive-and-repetitive behaviors compared to Caucasians [31,32]. Vanegas in 2016, showed that the communication domain from the Spanish-language ADI-R did not distinguish between Latino children with ASD and children with developmental disabilities [32], affecting rates of sensitivity and specificity.…”
Section: Lilia Albores-gallomentioning
confidence: 99%
“…Conversely, those whom DSM-5 identifies as Level 1 ASD (previously labelled as Asperger's syndrome) will have verbal communication but poor social communication and some repetitive behaviour but the symptoms only became apparent after 12 months. A further study could usefully examine the correspondence between the algorithm items used in Iran and the indicators of ASD derived from DSM-5 as has been undertaken by Magaña and Vanegas (2017) for Latino children in the United States. This would also provide further evidence for the criterion validity of the ADI-R.…”
Section: Discussionmentioning
confidence: 99%